2020
DOI: 10.5863/1551-6776-25.7.617
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Two Fosphenytoin Loading Dose Regimens and Monitoring in Infants and Neonates Less Than Six Months of Age

Abstract: OBJECTIVES The objectives of the study were to compare the free serum concentrations after different fosphenytoin loading dose strategies in patients younger than 6 months old and to investigate the frequency of seizure cessation following a loading dose of fosphenytoin. METHODS This retrospective cohort study included neonates and infants admitted to a 150-bed children's hospital between August 1, 2014, and February 1, 2018. Patients were included if they were younger than 6 months old and had a postload free… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…There was initial concern that parenteral fosphenytoin administration may result in reduced serum levels of free phenytoin, as early studies of pharmacokinetics were in older children and adults. However, additional studies that included neonates demonstrated adequate levels of free phenytoin serum concentration after loading doses of fosphenytoin and similar times to conversion to phenytoin as adult patients [41,42]. Despite this, an additional challenge remains with enteral administration of phenytoin due to inconsistent (often limited) absorption and variability in serum free phenytoin levels [43].…”
Section: Fosphenytoin and Phenytoinmentioning
confidence: 99%
“…There was initial concern that parenteral fosphenytoin administration may result in reduced serum levels of free phenytoin, as early studies of pharmacokinetics were in older children and adults. However, additional studies that included neonates demonstrated adequate levels of free phenytoin serum concentration after loading doses of fosphenytoin and similar times to conversion to phenytoin as adult patients [41,42]. Despite this, an additional challenge remains with enteral administration of phenytoin due to inconsistent (often limited) absorption and variability in serum free phenytoin levels [43].…”
Section: Fosphenytoin and Phenytoinmentioning
confidence: 99%